Hydatid Cyst in Adductor Magnus: A Very Rare Presentation of Hydatid Disease (Nepalese Journal of Radiology, 2025)
Hydatid disease is caused by Echinococcus granulosus which may affect any part of the body but preferably liver and lungs are the most frequent sites. The incidence of intramuscular hydatid disease is extremely rare even in the endemic region. Radiological imaging has an important role in the diagnosis of hydatid disease. Although serology test has high false negative results positivity can add to diagnosis. Marginal excision and incisional biopsy are contraindicated due to the occurrence of dissemination and anaphylactic shock. Therefore, if the patient presents with isolated musculoskeletal swelling keep hydatid cyst as a differential diagnosis in the endemic region to avoid complications. Here we present a case of a middle-aged female with a history of upper medial right thigh swelling which later confirmed hydatid cyst in adductor magnus muscle with the help of radiological imaging and serology. She is managed with albendazole with precystectomy.